Acupuncture for chronic cancer-related pain: a systematic review and network meta-analysis protocol. Issue 10 (7th October 2020) - Yang, Jiao; Xu, Guixing; Yin, Zihan; Cheng, Ying; Sun, Sheng Ming; Zheng, Qianhua; Chen, Jiao; Liang, Fan-rong; Zhao, Ling
Abstract : Introduction: Chronic cancer-related pain is one of the most common excruciating symptom that can be caused by the cancer (by the primary tumour or by metastases) or by its treatment (surgery, chemotherapy and radiotherapy). Although multiple clinical trials and systematic reviews have suggested that acupuncture could be effective in treating chronic cancer-related pain, the comparative efficacy and safety of these acupuncture methods remains unclear. We, therefore, performed this study to evaluate and rank the efficacy and safety of different acupuncture methods for chronic cancer-related pain. Methods and analysis: Seven databases will be searched, including Cochrane Library, MEDLINE, Embase, Chinese National Knowledge Infrastructure (CNKI), Wanfang Database, the Chongqing VIP Chinese Science and Technology Periodical Database and Chinese Biomedical Literature Database (CBM) from their inception to March 2020. The primary outcome is the change of pain intensity. Bayesian network meta-analysis will be conducted using software R3.5.1. Finally, we will use the Grading of Recommendations Assessment, Development and Evaluation System (GRADE) to assess the quality of evidence. Ethics and dissemination: Ethical approval is not required for literature-based studies. The results will be disseminated through peer-reviewed publication. PROSPERO registration number: CRD42020165747